EXPERIMENTAL STUDY OF THE CHRONIC TOXICITY OF THE TRIBULEPIL COLLECTION - Z.B. Ganieva; G.D. Reynazarova; Z.T. Fayzieva; Z.U. Usmanova (Scholar Express Journals, 2021)
The study of the chronic toxicity of the Tribulepil collection developed at the Tashkent Pharmaceutical Institute was carried out. Tribulepil collection was administered orally daily for 3 months, in single doses of 25 ml/kg, 50 ml/kg and 100 ml/kg. During the study, the body weight of the animals was determined, and a clinical blood test was performed. During the autopsy, the mass coefficients of the heart, liver, kidneys, stomach, testes and uterus were determined, and a pathomorphological examination of the internal organs was performed. It is shown that with prolonged administration, the collection of "Tribulepil" in 50 ml / kg and 100 ml / kg doses causes a delay in body weight gain. The pathomorphological examination established the absence of toxic effects on parenchymal organs and, in particular, on the genitals, only the presence of signs of circulatory disorders is noted only in the group with the use of the maximum (250 ml/kg) dose and only in females.
Keywords: Tribulepil; chronic toxicity; preclinical studies; mice